The Development Benefits and Risks of Recreational Parkour Sports in The Freerun Flow it Parkour Community - Claudia Salsabillah (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to explore the development, benefits, and risks of parkour as a recreational sport in the Parkour Freerun Flow It community in Pekanbaru. It focuses on the community's progress, the physical and mental benefits, and the potential risks associated with the sport. Methodology: This study used a qualitative method with purposive sampling. Data were collected through direct observation, semi-structured interviews, and documentation. The subjects consisted of community members and experts, including athletes, therapists, and medical professionals. Data analysis followed the Miles and Huberman model: data reduction, data display, and conclusion drawing. Main Findings: The study found a decline in interest and training intensity within the parkour community due to limited training facilities and lack of institutional support. Despite this, parkour offers significant benefits such as improved physical fitness, mental resilience, and self-confidence. Risks include minor to severe injuries, particularly if warm-ups are neglected. Younger practitioners are especially vulnerable due to underdeveloped joints and bones. Novelty/Originality of this study: This study contributes to the understanding of parkour as an emerging recreational sport in Indonesia. It uniquely documents the evolution and current state of a regional parkour community, highlighting the dual nature of parkour as both physically beneficial and potentially hazardous. It offers insights for policymakers to better support urban recreational sports.